Effectiveness of authentic performance tasks: The case of a special education course - Ufuk Uluçınar; Erkan Dinç (Journal of Pedagogical Research, 2021)
Designed as participatory action research, this study aims to develop authentic tasks as assessment and evaluation activities in an undergraduate special education course, and to examine the impact of these tasks on students' experiences, viewpoints and feelings during the implementation processes. The study group was comprised of 205 student teachers collaboratively working in groups. The participants prepared forty separate mini research projects in relation to special education and students with special needs. Research data was collected through collective research diaries, in which the participants reflected their experiences, thoughts and feelings in relation to the performance tasks they took part in. A qualitative content analysis was carried out to examine the available data, which was accompanied by constant comparative analysis procedures to ensure the reliability of the analysis processes. The research findings show that authentic performance tasks improve student teachers' professional development, help them to enhance their repertoire on research, methodology and science process skills, and develop their skills of self-confidence, self-efficacy, communication, interaction and the use of technology. The results indicate that the performance tasks are fun, innovative, motivating and educative for the participants. Therefore, they have living experiences contributing to them from various aspects.